2023
DOI: 10.3390/su15108423
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Community Energy Business Models from an Institutional Perspective: Intermediaries and Policy Instruments in Selected Cases of Developing and Developed Countries

Abstract: Community energy development and the empowerment of customers as producers are the main contributors to decentralized market solutions in energy transition policy. Despite the growing literature on community energy projects from the perspectives of various business models, drivers, and barriers, few studies display the impact of institutional factors on the community energy business model configuration. Using insights from Ostrom’s institutional framework, this study develops a conceptual framework comprising … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 58 publications
(109 reference statements)
0
1
0
Order By: Relevance
“…Market-pull policies such as energy taxes are politically controversial due to the expenses imposed on vulnerable consumers, and energy efficiency regulations should be adequately strong and stringent to the extent that they can impede the "rebound effects" of more direct and indirect consumption of energy sources. In addition, the concept of "technology spillovers" means that the benefits of patents and innovation are not restricted to only innovator firms or institutions, and hence investors are not normally interested in private RD&D foundations [108]. Taking into account the above-mentioned obstacles to energy transition, it is suggested that future studies could examine the challenges of energy transition considering the hindrance of technology development, supportive policies, and renewable energy deployment.…”
Section: Future Researchmentioning
confidence: 99%
“…Market-pull policies such as energy taxes are politically controversial due to the expenses imposed on vulnerable consumers, and energy efficiency regulations should be adequately strong and stringent to the extent that they can impede the "rebound effects" of more direct and indirect consumption of energy sources. In addition, the concept of "technology spillovers" means that the benefits of patents and innovation are not restricted to only innovator firms or institutions, and hence investors are not normally interested in private RD&D foundations [108]. Taking into account the above-mentioned obstacles to energy transition, it is suggested that future studies could examine the challenges of energy transition considering the hindrance of technology development, supportive policies, and renewable energy deployment.…”
Section: Future Researchmentioning
confidence: 99%